An Ethnobotanical Assessment of Medicinal Uses of Edible Plants in Malappuram District, Kerala, India (International Journal of Food and Nutritional Sciences, 2022)
Ethnobotanical investigation is essential for documenting and preserving the rapidly falling traditional knowledge of medicinal plants. The present study aims to document the traditional knowledge about medicinal uses of edible plants in Malappuram district, Kerala, India. Ethnomedicinal data was gathered from 16 informants of Cholanaikkan tribes in Nilambur forest through semi structured interview. A total of 42 edible plant species were mentioned by informants as medicinal. Fruits (44%) are the most preferably used plant part for herbal preparation. The study revealed that Phyllanthus emblica L. has the highest use value (UV=0.87), showing its significant use among the tribes. It is observed that the increasing significance of allopathic medicine and modernization caused many traditional practices to be at risk of being lost. A critical analysis of traditional knowledge concerning therapeutically important wild edible plants is urgently needed, to conserve this valuable cultural heritage and to potentially facilitate future advancements in drug discovery.